(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
Introduction. Humic substances affect plants directly or indirectly. The indirect effect is associated with improving the water-physical properties of the soil, activating microflora, influencing the migration of nutrients, and binding toxic agents (pesticides, heavy metals). Humic substances have a direct comprehensive effect on plant growth processes, i.e., they regulate them. The effect of humic fertilizers on plants is complex and multi-stage, covering the entire vegetation period. With humic substances, a certain amount of nutrients enters the plant — nitrogen, phosphorus, potassium, calcium, sulfur, and other microelements, as well as amino acids, vitamins, and growth substances. In addition, humates improve the plant’s uptake of sugars, amino acids, vitamins, and hormones from the soil. They accelerate water uptake and oxygen absorption by plants, which ultimately intensifies plant respiration. As a result of enhanced respiration, cell division, photosynthesis, protein synthesis, and the growth of the root system and above-ground mass are accelerated, the yield of dry matter increases, and, consequently, the overall vitality of plants improves. All this ultimately leads to enhanced growth, increased plant productivity, and improved product quality. Humates act as organic fertilizers and plant growth regulators. Analysis of recent studies and publications. In modern farming systems, there is a certain instability in the effectiveness of basic fertilization, which is a consequence of unbalanced prices for agricultural products and chemical industry products, the use of mainly minimal tillage systems, and the almost complete absence of a stable structure of cultivated areas. A partial solution to the problem of insufficient supply of nutrients to plants is the use of foliar feeding, which, according to many researchers, is effective in the cultivation of most crops [2]. Foliar feeding is particularly effective in unfavorable weather conditions and other factors that reduce the availability of nutrients from the soil: humidity and temperature indicators, soil pH, etc. In this case, foliar feeding stimulates the absorption of nutrients from the soil. Foliar feeding increases the intensity of chlorophyll synthesis in the leaves, contributing to their rich green color, which in turn stimulates root growth, sugar secretion, and the growth of microorganisms that provide the synthesis of auxins and other root-stimulating substances. With the increase in cellular gas exchange, the amount of moisture absorbed by the roots increases, and thus the process of absorbing nutrients from the soil solution is activated. In most cases, foliar feeding will be more effective if it is carried out several times – at the beginning and during the growing season of crops. A study of the effect of different timing of foliar feeding [2] on some biometric indicators of plants and sunflower seed yield showed that even a single application of foliar feeding stimulates the growth and development of sunflower plants. Feeding sunflowers with potassium humate is a useful tool for improving the growing conditions of this important agricultural crop and increasing its yield. Potassium humate for sunflowers is an effective organic-mineral fertilizer, the use of which contributes to improving the overall health of the plant and increasing its yield. Its advantages also include: stimulation of root system growth, improvement of soil structure and water retention capacity, activation of nutrient exchange, strengthening of the immune system, and stress resistance. The absorption of nutrients through the leaves and their subsequent assimilation depend largely on the level of root nutrition and, conversely, foliar feeding can have a direct or indirect effect on the absorption of minerals by the roots and their subsequent use by the plant. Therefore, foliar feeding should be considered not only as a way to increase the level of minerals, which, in turn, is a supplement to the usual root feeding, but also as a way to correct the latter, since this way it is possible to enhance its positive effect on the yield and quality of products [12]. Materials and methods. The experimental plots were established on the fields of Agroexpert LLC in the Kharkiv district of the Kharkiv region (2024) and on the Dokuchaevske experimental field of the State Biotechnological University in the Kharkiv district of the Kharkiv region (2025). Growth biostimulants (fertilizers) manufactured by Pesticide EOOD (Bulgaria) were used for the research. Below is a list and brief description of the products that were tested. Sunflower predecessors: 2024 – grain corn; 2025 – naked oats. Fertilizers: 2024 and 2025 – top dressing with 34 kg of nitrogen (100 kg NH4NO3); Culture – 2024 sunflower commercial hybrid MAS 920 CP 2025 sunflower commercial hybrid MAS 85 Research results and discussion. Studies have shown that foliar application of humic biostimulants, both as a single treatment (2 l/ha) and as two treatments (2+2 l/ha), on sunflower crops (commercial hybrid MAS 920 CP) in the arid climate of 2024, led to a reduction in plant temperature stress and contributed to some growth in the size of sunflower baskets. In the more humid conditions of 2025, a positive effect was also noted from the foliar application of humic biostimulants at a dose of 2 l/ha on the development of sunflower heads (commercial hybrid MAS 85), but unlike in 2024, no significant increase in the diameter of the baskets was observed when they were used twice (2+2 l/ha). A study of the effect of foliar application of the tested biostimulants produced by Pesticide EOOD (Bulgaria) on the yield of the commercial sunflower hybrid MAS 920 CP in the arid climatic conditions of 2024 showed the feasibility of a single application at a dose of 2 l/ha. A similar dependence was established for the more humid conditions of 2025 for the commercial sunflower hybrid MAS 85. Conclusions. Summarizing the results of two years of research on the effect of humic biostimulants produced by Pesticide EOOD on the growth and development of sunflowers, it can be concluded that these preparations should be considered not only as a source of macro- and microelements for plants, but also as an anti-stress agent in the arid climate of the Eastern Forest-Steppe of Ukraine. Continuing this research will make it possible to develop methods and means of counteracting global climate change.